10Be dating reveals early-middle Holocene age of the Drygalski Moraines in central West Greenland. (1st September 2016) - Cronauer, Sandra L.; Briner, Jason P.; Kelley, Samuel E.; Zimmerman, Susan R.H.; Morlighem, Mathieu
Abstract: We reconstruct the history of the Greenland Ice Sheet margin on the Nuussuaq Peninsula in central West Greenland through the Holocene using lake sediment analysis and cosmogenic 10 Be exposure dating of the prominent Drygalski Moraines. Erratics perched on bedrock outboard of the Drygalski Moraines constrain local deglaciation to ∼9.9 ± 0.6 ka (n = 2). Three Drygalski Moraine crests yield mean 10 Be ages of 8.6 ± 0.4 ka (n = 2), 8.5 ± 0.2 ka (n = 3), and 7.6 ± 0.1 ka (n = 2) from outer to inner. Perched erratics between the inner two moraines average 7.8 ± 0.1 ka (n = 2) and are consistent with the moraine ages. Sediments from a proglacial lake with a catchment area extending an estimated 2 km beneath (inland of) the present ice sheet terminus constrain an ice sheet minimum extent from 5.4 ka to 0.6 ka. The moraine chronology paired with the lake sediment stratigraphy reveals that the ice margin likely remained within ∼2 km of its present position from ∼9.9 to 5.4 ka. This unexpected early Holocene stability, preceded by rapid ice retreat and followed by minimum ice extent between ∼5.4 and 0.6 ka, contrasts with many records of early Holocene warmth and the Northern Hemisphere summer insolation maximum. We suggest ice margin stability may instead be tied to adjacent ocean temperatures, which reached an optimum in the middle Holocene. Highlights: This study uses 10 Be dating to determine the age of the Drygalski Moraines in central West Greenland. Three moraine crests have early Holocene ages and local deglaciation occurred at ∼9.9 ka. Lake sediment analysis constrains the Greenland Ice Sheet margin's minimum Holocene extent from ∼5.4 to ∼0.6 ka. The Greenland Ice Sheet margin remained within a few km of its present position from 9.9 to 5.4 ka, consistent with coastal paleoclimate records.